Weather Information for Tribune, KS 2023 - Amanda Burnett (Kansas Agricultural Experiment Station Research Reports, 2024)
Summary of 2023 weather for research conducted at the research locations included in the 2024 Western Kansas Agricultural Research report.
Keywords: weather; precipitation; Tribune; Kansas; temperature; wind; evaporation